2007
DOI: 10.1063/1.2717553
|View full text |Cite
|
Sign up to set email alerts
|

Thickness effects on the electrical characteristics of Ba0.7Sr0.3TiO3 capacitors with nano-Cr interlayer

Abstract: structure was sputtered sequentially onto Pt/ Ti/ SiO 2 / Si substrate. With the insertion of a 2 nm Cr interlayer, the temperature coefficient of capacitance of the BST/Cr/BST dielectric is about 69% lower than that of BST monolayer dielectric. The dielectric constant and dissipation factor as the function of Cr thickness are studied. X-ray diffraction patterns, the analysis results of energy dispersive spectroscopy, and the survey scan profiles of Auger electron spectroscopy reveal the formation of a TiO 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…At present, materials such as Ba x Sr 1−x TiO 3 (BST), BaZr x Ti 1−x O 3 (BZT), PbZr x Ti 1−x O 3 (PZT), and Pb 1−x Ba x TiO 3 (PBT) systems have been intensively investigated [7][8][9][10][11][12][13]. Recently, Somiya et al [14] reported that Pb x Sr 1−x TiO 3 (PST) has better properties than BST.…”
Section: Introductionmentioning
confidence: 97%
“…At present, materials such as Ba x Sr 1−x TiO 3 (BST), BaZr x Ti 1−x O 3 (BZT), PbZr x Ti 1−x O 3 (PZT), and Pb 1−x Ba x TiO 3 (PBT) systems have been intensively investigated [7][8][9][10][11][12][13]. Recently, Somiya et al [14] reported that Pb x Sr 1−x TiO 3 (PST) has better properties than BST.…”
Section: Introductionmentioning
confidence: 97%
“…1(b)-(e). Our previous work suggests that a β-TiO 2 secondary phase is formed after the BST/Cr/BST dielectrics are annealed in O 2 for 1 h [7], [8]. Hence, the thin layer on top of the BST is TiO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Normally, compared with the bulk materials, the quality of crystallization of the film is poorer, dielectric loss is higher, leakage current is bigger. Therefore, many researchers have studied the influence of deposition method, 7-10 deposition temperature, 11,12 film thickness, 13,14 and different substrates 15 on Ba x Sr 1−x TiO 3 film fabrication, so that the property of the Ba x Sr 1−x TiO 3 film capacitor has been modified for tunable microwave device applications. As one of the most commonly used deposition methods in preparing oxide films, pulsed laser deposition (PLD) usually uses oxygen as ambient gas to avoid oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%